Disposição de lodo de ete de indústria alimentícia no solo: Efeitos na água subterrânea - Pereira, Ana Carolina Amaral [UNESP]; Garcia, Marcelo Loureiro [UNESP] (My University, 2017)
Sludge from wastewater treatment plants usually contains high levels of organic matter and nutrients, and therefore it can be used as fertilizer and soil conditioner. However, its disposal on the soil has to be properly managed because it can contain contaminants. The aim of this work was to investigate the effects of soil disposal of food industry sludge on the groundwater. The results show a higher concentration of barium and zinc in the groundwater under the influence of the sludge disposal in comparison with the control area, but it is not clear whether this difference is due to the sludge application on the soil. It was not observed scenario change for toxic organic substances and microbiological indicators. All groundwater parameters met the water quality standards set by Brazilian Federal Regulations (Resolução CONAMA nº 420/2009 and Portaria MS nº 2914/2011).
Disposal of sludge from food industry wastewater treatment plant on soil: Effects on groundwater
Keywords: Groundwater; Sludge disposal on soil; Wastewater sludge